Effects of televised alcohol advertisements on the drinking behaviour of youth:a case study of Praktiseer community in Greater Tubatse Municipality - Mapulane, Mawethu Glemar (University of Limpopo, 2014)
This study investigates the effects of televised alcohol advertisements on the drinking behaviour of youth in Praktiseer community of the Greater Tubatse Municipality. The nature and trends of alcohol consumption in South Africa are examined. The study also focuses on the impact of alcohol exposure, and the costs alcohol abuse can incur on the individual and society at large. The types of advertising models and the regulatory systems in advertising were identified. Data were collected through a self- administered questionnaire. The study hypothesised that the exposure to alcohol advertisements influences alcohol abuse among the youth. However, alcohol industry claims that the youth is not its niche market and hence should not be blamed for any abusive behaviour of alcohol by the youth. Just like the few studies interested in the effects of alcohol advertising, alcohol exposure and alcohol abuse, the present study also reveals that televised alcohol advertisements have a great influence in alcohol consumption among the youth in Praktiseer community.
Thesis ( M.A. (Media Studies)) --University of Limpopo, 2014
Keywords: Alcohol advertisements; Drinking behaviour; Youth; Youth-Alcohol use -- South Africa - Praktiseer; Alcoholic beverages -- Advertising